Pugicorn - Matilda Rose (London; Hodder Children's Books, 2020)
He's a dog . . . in a unicorns' world! Every year, young princesses and princes arrive at Mrs Paws' Magic Pet shop to pick a perfect unicorn pet. But this year Princess Ava has arrived too late. There are no unicorns left . . . only PUGICORN. He's short and hairy. He can't sit still or gallop gracefully - and he certainly can't leap over rainbows. Can a pugicorn ever be a princess's best friend?
Keywords: Picture books for children